Primary care biomarkers and dementia in people of the Torres Strait, Australia: extended data analysis - Thompson, Fintan; Russell, Sarah; Quigley, Rachel; McDonald, Malcolm; Sagigi, Betty; Taylor, Sean; Campbell, Sandy; Schmidt, Barbara; Esterman, Adrian; Harriss, Linton R.; Miller, Gavin; Mills, Phillip; et al. (Frontiers in Dementia, 2023)
Objective: Dementia disproportionately affects First Nations populations. Biomarkers collected in primary care may assist with determining dementia risk. Our previous underpowered study showed some suggestive associations between baseline biomarkers with follow-up dementia or cognitive impairment. The current study extended this work with a larger linked dataset.Study Design and Setting: Probabilistic data linkage was used to combine four baseline datasets with one follow-up assessment of dementia status 0-20 years later in a First Nations population in Australia. Mixed Effects Generalized Linear Regression models were used to test associations between baseline measures and follow-up status, accounting for repeated measures within individuals.Results: Linked data were available for 88 individuals, with 101-279 baseline observations, depending on the type of measure. Higher urinary albumin to creatine ratio was associated with greater risk of cognitive impairment/dementia, whereas body weight and key lipid markers were negatively associated. Lower body weight, triglycerides, total cholesterol, and very lowdensity lipoprotein cholesterol (LDL), and very-low LDL were associated with greater risk of cognitive impairment/dementia, as was higher urinary albumin to creatine ratio. There was no clear trend when these associations were examined by timing of measurement (i.e., ≤10 years or >10 years before a dementia assessment).The results of this study support findings from our previous work and indicate suggest that microalbuminuria can be an early indicator of dementia risk in this population.The weight and lipid profile findings reflect the mixed results in the published literature and require further investigation and interpretation. kidney function measures collected in primary care may be useful for indicating dementia risk in this population.